Small business financial growth: from theoretical perspective - Azam, S. M. Ferdous; Abdullah, Moha Asri; Abdul Razak, Dzuljastri; Hamdan, Hamdino (2014)
This conceptual paper aims to draw a structure based on three core theories namely Knowledge Management Theory (KMT), Life Cycle Theory (LCT) and Resource-Based View (RBV) for small business financial growth. To do so, the paper reviews the most cited articles on the topic published in academic journals to analyze those theories for small business financial growth. The theoretical illustration helps to understand how the fundamental theories are related with small business that promotes further theoretical and empirical platforms in the areas of financial growth for small business. Keywords: Small Business, Financial Growth, Knowledge Management Theory (KMT), Life Cycle Theory (LCT), Resource-Based View (RBV)